Enhancing the catalytic efficiency of the Heck coupling reaction by forming 5 nm Pd octahedrons using kinetic control - Long, Ran; Wu, Di; Li, Yaping; Bai, Yu; Wang, Chengming; Song, Li; Xiong, Yujie (Nano research, 2015)
Heterogeneous catalysis occurs through a process of interfacial reactions; therefore, both surface facet and size control can increase catalytic efficiency. Octahedral Pd nanocrystals, enclosed by {111} facets, should be the ideal geometrical shape for Heck coupling reactions; however, it is challenging to synthesize 5 nm Pd octahedrons with a relatively uniform size distribution using existing capping-agent techniques. Here, we used palladium as a model system to investigate how the kinetics of atomic addition could be precisely controlled using a syringe pump. As a result, our method produced Pd octahedrons as small as 5 nm, which increased the catalytic efficiency of Heck coupling reactions while reducing the weight of catalyst used.